(untitled) (Applied Biological Research, 2023)
In bovines, dystocia incidence is quite high than other farm animal species (Dutt et al., 2021). Fetal anomalies and monstrosities of various kinds cause dystocia in cattle (Mir et al., 2015) and buffaloes (Shukla et al., 2007). The congenital abnormalities of foetus with structure and function may occur at birth and are relatively less frequent in bovines (Rahman et al., 2006). The incidence of congenital defects in calves ranges from 2 to 3.5%, of which 24% cases are musculo-skeletal defects (Aiello, 2000). Congenital skeletal deformities, also called dysostoses, are the defects arising from the errors during development and are characterized by abnormal growth of individual bones or part of bones. The organogenesis is the period of gestation highly susceptibility to various kinds of teratogens. The present report presents two cases of dystocia due to congenital fetal anomalies in Murrah buffaloes.